From Carmageddon and Invizimals to SimCity and Digimon: Blending Patterns in Videogame Titles - López-Rúa, Paula (Complutense Journal of English Studies, 2019)
This paper delves into the structure and motivations of blending by reporting on the results of the analysis of a corpus of 80 blends gathered from the field of videogaming. The starting point will be a multidimensional description based on a set of parameters and values drawn on previous works by, among others, Kemmer (2000), Ronneberger-Sibold (2006) and Mattiello (2013). In accordance with the principles of Prototype Theory (Lakoff 1987; Langacker 1987), the combination of values displayed by the items results in an overall degree of typicality and will allow their location in the centre or the periphery of the category. The theoretical framework will be put into practice in the analysis of a corpus of blends naming videogames. Most of them are found to be prototypical items, the most common type being the so-called "overlapping" blend (Splatoon: splat + platoon). Lastly, concerning the motivations for the creation of blends in this particular field, these items succeed in economically capturing key features of the game so as to awaken the interest of potential buyers. Moreover, blends anticipate the humorous, puzzling or creative qualities of the game they name and wink at the players’ inventiveness to work out rules.